The role of Fusobacterium nucleatum in macrophage M2 polarization and NF-κB pathway activation in colorectal cancer - Zheng, Wei; Wang, Yuxin; Sun, Haoyang; Bao, Surina; Ge, Shuai; Quan, Chunshan (Frontiers in Immunology, 2025)
Fusobacterium nucleatum is strongly linked to colorectal cancer (CRC) progression, but its mechanisms for influencing macrophage polarization and tumor development are not well understood. We established an in vitro model of F. nucleatum infection in RAW264.7 macrophages to investigate these processes. Macrophage polarization was evaluated using scanning electron microscopy (SEM), real-time quantitative PCR (RT-qPCR), and immunofluorescence staining. RNA sequencing (RNA-Seq) identified differentially expressed genes (DEGs) and enriched pathways, focusing on the role of the NF-κB signaling pathway in macrophage polarization. F. nucleatum infection induced M2 polarization in RAW264.7 macrophages, as confirmed by SEM analysis and RT-qPCR validation. A total of 2,029 DEGs were identified after F. nucleatum infection, with 763 upregulated and 1,266 downregulated. GO and KEGG enrichment analysis showed that cytokine-cytokine receptor interaction, TNF signaling, and NF-κB signaling pathways are upregulated in macrophages after F. nucleatum infection, indicating enhanced cytokine activity and immune response. Key genes (Nfkb1, Nfkb2, Malt, Lta, Ltb, Tnf) and proteins (P50, P100) in the NF-κB pathway are upregulated, indicating the crucial role of the NF-κB pathway in M2 macrophage polarization. This study offers crucial evidence regarding the role of the NF-κB signaling pathway in modulating F. nucleatum-induced macrophage M2 polarization, underscoring its significance in the progression of colorectal cancer.